Práticas discursivas, mulheres e memórias: identidade e manifestações culturais em Nova Prata - Gonçalves, Iverton Gessé Ribeiro (2015)
The theme of this research entitled Discursive Practice, Women and Memory: Identity and Cultural Manifestations in Nova Prata is bounded to analyze women discursive practice, within the semantics restriction system that regulates the discourse of the italian imigration in Nova Prata, particularly, the scenography and the discursive ethos that can be both seized from this discourse. The goal this study heads towards is to interpret the scenographies built to serve the cultural expressions on discourse of Italian immigration descendant women, as well as to understand the discursive éthe resulting from this enunciation movement as women identity constructs in Italianity. The conceptions of culture, symbolic representation systems and symbolic power, postulated by Bosi (1992), Bourdieu (1974, 1989), De Certeau (1994, 1995) and Geertz (2008), and the identity descriptions presented in the studies of Bauman (2005), Canclini (1995), Hall (2006, 2013) and Woodward (2013), compound the first foundation of the theoretical framework on which this study is developed. The guidance for the global semantics study and the theoretical categories of the enunciation scenography and discursive ethos, proposed by Maingueneau (1984/2008a, 1987/1997, 2000/2013), build up the second foundation that supports this research. The justification of this study is given by the possibility of understanding culture as a semiotic network working towards a symbolic power. The identity, a discursive place provided by this semiotic network, is only lived through discourse. The study of the global semantics gives us the opportunity to interpret the cultural manifestations and the identity marks by means of the discursive plans and the enunciation entwinement put forward by scenography and by discursive ethos. The corpus of this research is composed of a documentary video produced by the Nova Prata's Educational and Cultural City Council and entitled Mulheres e Memórias (Women and Memory). Related to its goals, the research is featured as exploratory-descriptive; bibliographic and documentary regarding to its technical procedures and it is classified as qualitative when related to its approach. The symbolic representation system of semanticsrestrictions reveals, in the discourse of Italian immigration woman, the need of the enunciator to legitimate herself through the hard work for the community, the matrimony as a profession of faith and the family constitution. The scenography of this discourse tries to legitimate itself in a founder deixis that recalls the immigration suffering and enhances the immigrant in the building of an heroic and zealous ethos.